2019
DOI: 10.1007/s00438-019-01614-3
|View full text |Cite|
|
Sign up to set email alerts
|

A high-quality cucumber genome assembly enhances computational comparative genomics

Abstract: Genetic variation is expressed by the presence of polymorphisms in compared genomes of individuals that can be transferred to next generations. The aim of this work was to reveal genome dynamics by predicting polymorphisms among the genomes of three individuals of the highly inbred B10 cucumber (Cucumis sativus L.) line. In this study, bioinformatic comparative genomics was used to uncover cucumber genome dynamics (also called real-time evolution). We obtained a new genome draft assembly from long single molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 71 publications
0
35
0
1
Order By: Relevance
“…The upor down-regulated DEGs were specific to individual groups of samples representing a single line (S1, S2, or S3), but the remainder of the genes were similar to the control B10 line. Nonlinear PCA for all genes (21661) detected in the cucumber reference genome B10v3 (Osipowski et al 2020) revealed structure in the data, with obvious subgroups of the somaclonal lines, especially with regard to DEGs (Fig. 3e, f).…”
Section: Identification Of Degsmentioning
confidence: 98%
See 2 more Smart Citations
“…The upor down-regulated DEGs were specific to individual groups of samples representing a single line (S1, S2, or S3), but the remainder of the genes were similar to the control B10 line. Nonlinear PCA for all genes (21661) detected in the cucumber reference genome B10v3 (Osipowski et al 2020) revealed structure in the data, with obvious subgroups of the somaclonal lines, especially with regard to DEGs (Fig. 3e, f).…”
Section: Identification Of Degsmentioning
confidence: 98%
“…To analyze gene expression and identify DEGs in somaclonal lines and B10 control plants, we performed transcriptome assembly with additional data from PCC Genomics (Osipowski et al 2020). As a reference genome we used the cucumber genomic sequence B10v3 (Gen-Bank: LKUO00000000).…”
Section: Rna-seq Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The C. sativus genome sequence B10v3 (GenBank: LKUO00000000) and annotated genes were retrieved from PCC Genomics (Polish Consortium of Cucumber Genome Sequencing) [26]). The RNA-seq reads from this project, together with transcriptomic data from previous PCC Genomics research, were used to generate the de novo transcriptome assembly [26]. Gene expression was analyzed by comparing the transcriptome data between the transgenic and wild-type plants.…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…For example, in Arabidopsis, CNVs could be observed among individuals separated by only one generation; numerous CNVs affecting hundreds of genes had already originated after only five generations [59][60][61] . In cucumber, Osipowski et al 62 reported 626 CNVs among three individual plants derived from a common ancestor after 21 or 22 generations of continuous self-pollination. CNVs could be generated through different genetic mechanisms including nonallelic homologous recombination (NAHR) or unequal crossing over (UCO), which results from aberrant homology recognition during homology-based DNA repair or meiosis 61,63 .…”
Section: Introductionmentioning
confidence: 99%